If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6h + -3 = 15 Reorder the terms: -3 + 6h = 15 Solving -3 + 6h = 15 Solving for variable 'h'. Move all terms containing h to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + 6h = 15 + 3 Combine like terms: -3 + 3 = 0 0 + 6h = 15 + 3 6h = 15 + 3 Combine like terms: 15 + 3 = 18 6h = 18 Divide each side by '6'. h = 3 Simplifying h = 3
| 3g+6=15 | | x/3+x/12=15/4 | | 4/x=5/-6 | | 3n^2+6n-13=0 | | R=ir | | (2x-3)*(2x-3)=25 | | 6+6x=4x-10 | | Y=(x-2)(x+3) | | 4sint+3cost=0 | | 3x+30=2x-10 | | Y=(x+4)(x+1) | | Y=(x+4)(c+1) | | 12w=14 | | w/4=7.2 | | -7x+5=1-3x | | 23x+14-14=7x-2-14 | | 2y(8-2y)= | | Sinx+x*cosx-sinx=0 | | F(x)=2x^3-5x^2+4-1 | | 7(w+10)+6=12w-12 | | 4x*x+29x-24=0 | | 7x-14=4x-23 | | xy+yf-dx=0 | | 11=9(a-12) | | 25t^2+11t+9=0 | | w/1=8.5 | | 18x3/6 | | ln(x-5)-ln(x)=6 | | 8w=11 | | 6x+5=12-2x | | 12x-7+3x=53 | | 3x+6x-13=14 |